Overall Survival Benefit in Patients With Rituximab-Refractory Indolent Non-Hodgkin Lymphoma Who Received Obinutuzumab Plus Bendamustine Induction and Obinutuzumab Maintenance in the GADOLIN Study - Cheson, Bruce D; Chua, Neil; Mayer, Jiri; Dueck, Greg; Trněný, Marek; Bouabdallah, Kamal; Fowler, Nathan; Delwail, Vincent; Press, Oliver; Salles, Gilles; Gribben, John G; Lennard, Anne; et al. (Journal of clinical oncology, 2018)
Purpose To perform an updated analysis of the randomized phase III GADOLIN trial in patients with rituximab-refractory indolent non-Hodgkin lymphoma treated with obinutuzumab (GA101; G) and bendamustine (B). Patients and Methods Patients with histologically documented, rituximab-refractory CD20+ indolent non-Hodgkin lymphoma received G 1,000 mg (days 1, 8, and 15, cycle 1; day 1, cycles 2 to 6) plus B 90 mg/m2/d (days 1 and 2, all cycles) or B 120 mg/m2/d monotherapy. Patients who did not experience disease progression with G-B received G maintenance (1,000 mg every 2 months) for up to 2 years. The primary end point was progression-free survival (PFS). Results Of 413 randomly assigned patients (intention-to-treat [ITT]: G-B, n = 204; B monotherapy, n = 209), 335 had follicular lymphoma (FL; G-B, n = 164; B monotherapy, n = 171). After a median follow-up of 31.8 months, median PFS in ITT patients was 25.8 months (G-B) and 14.1 months (B monotherapy; hazard ratio [HR], 0.57; 95% CI, 0.44 to 0.73; P < .001). Overall survival (OS) also was prolonged (HR, 0.67; 95% CI, 0.47 to 0.96; P = .027). PFS and OS benefits were similar in patients with FL. Grade 3 to 5 adverse events (AEs) were reported by 148 (72.5%) and 133 (65.5%) patients in the G-B and B monotherapy arms, respectively, most commonly neutropenia (G-B, 34.8%; B monotherapy, 27.1%), thrombocytopenia (10.8% and 15.8%), anemia (7.4% and 10.8%), and infusion-related reactions (9.3% and 3.4%). Serious AEs occurred in 89 G-B patients (43.6%) and 75 B monotherapy patients (36.9%); fatal AEs occurred in 16 (7.8%) and 13 (6.4%), respectively. Conclusion This updated analysis confirms the PFS benefit for G-B shown in the primary analysis. A substantial OS benefit also was demonstrated in the ITT population and in patients with FL. Toxicity was similar for both treatments.
Keywords: senioři; senioři nad 80 let; udržovací chemoterapie; bendamustin hydrochlorid; Bendamustine Hydrochloride; doba přežití bez progrese choroby; Kaplan-Meier Estimate; Middle Aged; mužské pohlaví; Kaplanův-Meierův odhad; míra přežití; Adult; Lymphoma, Follicular; indukční chemoterapie; chemorezistence; Aged, 80 and over; Rituximab; ženské pohlaví; Humans; Drug Resistance, Neoplasm; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Survival Rate; Progression-Free Survival; rituximab; lidé středního věku; Induction Chemotherapy; Antineoplastic Combined Chemotherapy Protocols; Maintenance Chemotherapy; protokoly protinádorové kombinované chemoterapie; nehodgkinský lymfom; dospělí; Lymphoma, Non-Hodgkin; Female; Aged; folikulární lymfom; lidé; Male